Adherence to the Traditional Mediterranean Diet and Human Milk Composition: Rationale, Design, and Subject Characteristics of the MEDIDIET Study - Moro, Guido E.; Bertino, Enrico; Bravi, Francesca; Tonetto, Paola; Gatta, Alberto; Quitadamo, Pasqua A.; Salvatori, Gugliemo; Profeti, Claudio; Di Nicola, Paola; Decarli, Adriano; Ferraroni, Monica; Tavani, Alessandra; et al. (Frontiers in Pediatrics, 2019)
Introduction: The knowledge on how a lactating woman’s diet influences the composition of her breast milk is still very limited. In particular, no study has evaluated the role of adherence to the Mediterranean diet on human milk proprieties. Aim: We carried out an observational study, to investigate the influence mother’s adherence the Mediterranean diet on her breast milk composition. Methods: Between 2012 and 2014, 300 healthy mothers who exclusively breastfed their babies were enrolled from 5 centers across Italy. During a visit to the hospital center 6 weeks after childbirth these women were asked to provide a sample of their freshly expressed breast milk and to answer a series of questions on personal factors. The application of a validated food frequency questionnaire made up the biggest part of these interviews. Milk was collected and then stored until chemical analyses were performed. The study has been registered (Trial Registration: Dutch Trial register NTR3468). Descriptive analyses on baseline characteristics of mothers and babies were carried out on the participants, overall and stratified by center. Results: the participants had a mean age of 33 years (SD=4.06), a pre-pregnacy BMI of 22.3 (SD=3.22). Forty-seven percent gave birth to their firstborn, 40% had 2 children, 13% had 3 or more children. Babies had a mean birth weight of 3324 g (DS=389), and a mean length of 51 cm (SD=1.94). Fifty-three percent were males. Conclusion: The present work provides the general description and the characteristics of mothers and babies included in the MediDiet study.